2012
DOI: 10.26719/2012.18.3.255
|View full text |Cite
|
Sign up to set email alerts
|

Middle ear and hearing disorders of schoolchildren aged 7–10 years in South Sinai, Egypt

Abstract: Hearing loss among schoolchildren in developing countries is reported to be a significant health problem. Data on child hearing loss in South Sinai, a remote governorate of Egypt, are lacking. Middle ear diseases and hearing impairment were assessed among 453 primary-school children aged 7-10 years in South Sinai (906 ears). Otoscopic examination, tympanometry and pure tone audiometry (PTA) were done. Ear disease was found in 27.5% of the ears examined. The commonest cause was secretory otitis media (10.8%), f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
15
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 14 publications
5
15
2
1
Order By: Relevance
“…In the present study, the most observed alteration in the meatoscopy was excessive cerumen, which is reported in literature as one of the most frequent causes of alterations in preschool and school-age children 1 . Recent studies have found that the presence of excessive cerumen in the EAC was the most common alteration found in students [20][21][22] , which complies with the results in this study. However, in other researches 10,11,23,24 , there the prevalence of excessive cerumen was a higher than in this study.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, the most observed alteration in the meatoscopy was excessive cerumen, which is reported in literature as one of the most frequent causes of alterations in preschool and school-age children 1 . Recent studies have found that the presence of excessive cerumen in the EAC was the most common alteration found in students [20][21][22] , which complies with the results in this study. However, in other researches 10,11,23,24 , there the prevalence of excessive cerumen was a higher than in this study.…”
Section: Discussionsupporting
confidence: 82%
“…Thakur et al in which they reported that hearing loss was more in males than in females 27 . Regarding wax, prevalence was found more in girls 143 (26.19%) than in boys 95 (17.40%) which was similar to the study findings of G. Yamamah et al in which they reported that ear wax is more frequent in girls than in boys 28 .…”
Section: Discussionsupporting
confidence: 81%
“…A study conducted by Thakur et al reported that hearing impairment was found in 2% among children under 15 years of age 27 ,which is close to our study findings. Further in a study conducted in Saudia Arabia reported prevalence of hearing loss in school children of 6-12 years of age was 4.4% 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study done by Yamamah et al [11] out of 10.8 % cases of OME 8.5 % cases were having mild to moderate hearing loss and only 0.4 % cases were having severe hearing loss. On radiological examination, it was seen that 34.3 % children had adenoid grade 1, 35.8 % had grade 2 and 36.8 % had grade 3 adenoid hypertrophy.…”
Section: Discussionmentioning
confidence: 53%